2008
DOI: 10.1080/08916930802031579
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of unlocking the cardiac myosin molecule in human myocarditis and cardiomyopathies

Abstract: Myocarditis, often initiated by viral infection, may progress to autoimmune inflammatory heart disease, dilated cardiomyopathy and heart failure. Although cardiac myosin is a dominant autoantigen in animal models of myocarditis and is released from the heart during viral myocarditis, the characterization, role and significance of anti-cardiac myosin autoantibodies is poorly defined. In our study, we define the human cardiac myosin epitopes in human myocarditis and cardiomyopathies and establish a mechanism to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 54 publications
2
86
0
1
Order By: Relevance
“…Autoantibodies against cardiac α and β myosin heavy chain, mitochondrial antigens, adenine nucleotide translocator, cardiac β1 adrenergic receptor and M2 muscarinic receptor, anti-branched chain α-ketoacid dehydrogenase dihydrolipoyl transacylase, and other autoantigens might participate in the pathogenesis (Afanasyeva et al 2004;Li et al 2008). Immunization against cardiac myosin heavy chain or infusion of anti--myosin autoantibodies in susceptible mice have caused myocarditis (Mascaro-Blanco et al 2008;Rose 2008). Autoantibodies can cause apoptosis of cardiomyocytes or complement activation, direct cell-mediated cyotoxicity, or alter myocardial function (Afanasyeva et al 2004;Mascaro-Blanco et al 2008).…”
Section: Autoimmune Aspectsmentioning
confidence: 99%
“…Autoantibodies against cardiac α and β myosin heavy chain, mitochondrial antigens, adenine nucleotide translocator, cardiac β1 adrenergic receptor and M2 muscarinic receptor, anti-branched chain α-ketoacid dehydrogenase dihydrolipoyl transacylase, and other autoantigens might participate in the pathogenesis (Afanasyeva et al 2004;Li et al 2008). Immunization against cardiac myosin heavy chain or infusion of anti--myosin autoantibodies in susceptible mice have caused myocarditis (Mascaro-Blanco et al 2008;Rose 2008). Autoantibodies can cause apoptosis of cardiomyocytes or complement activation, direct cell-mediated cyotoxicity, or alter myocardial function (Afanasyeva et al 2004;Mascaro-Blanco et al 2008).…”
Section: Autoimmune Aspectsmentioning
confidence: 99%
“…Mimicry between microbial pathogens and host tissues may lead to the induction of antibodies which signal cells in an autoantibody-mediated cell signalling mechanism. The most recent studies have shown that crossreactive antibodies against cardiac myosin and the b adrenergic receptor in the heart can lead to induction and activation of protein kinase A signaling (Li, Heuser et al, 2006;Mascaro-Blanco et al, 2008). The passive transfer of autoantibodies which signal myocardial cells led to sites of apoptosis in the heart (Li et al, 2006).…”
Section: Mimicry Of T-and B-cell Epitopes B-cell Epitopesmentioning
confidence: 99%
“…The passive transfer of autoantibodies which signal myocardial cells led to sites of apoptosis in the heart (Li et al, 2006). Such pathogenic signalling autoantibodies may lead to dilated cardiomyopathy in humans (Mascaro-Blanco et al, 2008).…”
Section: Mimicry Of T-and B-cell Epitopes B-cell Epitopesmentioning
confidence: 99%
“…And the pathogenesis is similar to the second stage of VMC. Mascaro-Blanco et al (2008) found a new class of cross-reactive autoantibodies against human cardiac myosin, whose epitopes can also be widely considered as the diseasespecific peptide epitopes in cardiomyopathies. In addition, they pointed out that these epitopes were found primarily in the S2 region of the cardiac myosin rod as well as a mechanistic role of autoantibody in the disease pathogenesis.…”
Section: Liaomentioning
confidence: 99%